Driving for Fun? – A Comparison of Weekdays and Weekend Travel - Manuel Frondel; Colin Vance (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
Focusing on individual motorists in car-owning households in Germany, this paper econometrically investigates the determinants of automobile travel with the specific aim of quantifying the effects of fuel prices and person-level attributes on travel conducted over a five-day week and weekend. Our analysis is predicated on the notion that car use is an individual decision, albeit one that is dependent on intra-household allocation processes, thereby building on a growing body of literature that has identified the importance of socioeconomic factors such as employment status, gender, and the presence of children in determining both access to the car and distance driven. To capture this two-stage decision process, we employ the Two-Part Model, which consists of Probit and OLS estimators, and derive elasticity estimates that incorporate both the discrete and continuous choices pertaining to car use.With fuel price elasticity estimates ranging between -0.42 and -0.48, our results suggest raising prices via fuel taxes to be a promising energy conservation and climate protection measure.
Keywords: D13; Q41; 330; Automobile travel; Two-Part Model; interaction effects; Motorisierter Individualverkehr; Konsumentenverhalten; Benzin; Preis; Deutschland